Collection and Memory in Everything Is Illuminated by Liev Schreiber - Maia, Claudia (2015)
The film Everything Is Illuminated (2005), directed by Liev Schreiber and based on the novel up, Everything Is Illuminated, by Jonathan Safran Foer, tells the story of a young American Jew who travels to the Ukraine in search of his past. The collection for the protagonist of the film and to the woman he meets in Trachimbrod, survivor of a massacre that destroyed his entire family, is of fundamental importance. Both characters together objects as a way to combat the spread and oblivion, as well as Walter Benjamin argued about the collector. This fight is intrinsically linked to Jewish memory, constantly threatened by totalitarian regimes.